A Study Of Value Based Structural Model For E-alliances - Harandi, Amirpouyan Balali (2007)
In this paper a new e-value delivery structural model is suggested for e-alliances to visualize their necessary components andrequired elements. This paper examines different aspects and components of an electronic alliance and their relationship.